1987
DOI: 10.1152/ajpregu.1987.252.3.r599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuropeptide Y on ingestive behaviors in the rat

Abstract: Neuropeptide Y (NPY) is a potent stimulator of food and water intake in rats. NPY still increases food intake even after a 2-h delay in access to food after central injection. When two injections of NPY are given 2 h apart, the second injection produced a substantial increase in food intake. This suggests that tolerance to the NPY effect does not develop after a single injection of NPY. NPY increases moving and exploration in the absence of food when rats are in their home environment but not when tested in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 0 publications
8
73
0
Order By: Relevance
“…On the other hand, high doses of NPY and PYY seemed to induce hyperactivity in guinea-pigs, and one re¯ection of this activation is the increased amount of small meals consumed (Tables 2 and 3). Indeed, injections of NPY into frontal cortex or lateral brain ventricle in rats have been shown to increase locomotion and exploration (Levine & Morley, 1984;Morley et al, 1987b;Smialowski et al, 1992), although not in all studies (Heilig et al, 1988). Our observation that increased locomotion might be connected to Y 5 receptor stimulation is in agreement with the previous ®nding showing that the Y 5 antagonist, CGP 71683A, decreases exploratory behaviour in rats (Kask et al, 2001).…”
Section: British Journal Of Pharmacology Vol 135 (8)supporting
confidence: 92%
“…On the other hand, high doses of NPY and PYY seemed to induce hyperactivity in guinea-pigs, and one re¯ection of this activation is the increased amount of small meals consumed (Tables 2 and 3). Indeed, injections of NPY into frontal cortex or lateral brain ventricle in rats have been shown to increase locomotion and exploration (Levine & Morley, 1984;Morley et al, 1987b;Smialowski et al, 1992), although not in all studies (Heilig et al, 1988). Our observation that increased locomotion might be connected to Y 5 receptor stimulation is in agreement with the previous ®nding showing that the Y 5 antagonist, CGP 71683A, decreases exploratory behaviour in rats (Kask et al, 2001).…”
Section: British Journal Of Pharmacology Vol 135 (8)supporting
confidence: 92%
“…These increases occurred despite the fact that NPY--infused rats were prevented from overeating by pair--feeding with controls, and that there was no increase in body weight. Adrenalectomy abolished these NPY effects, in keeping with studies showing that other adipogenic effects of NPY are completely prevented or significantly attenuated by prior adrenalectomy in rats [16,23,29,31,34,37,43,45], and restored by specific glucocorticoid replacement [31,34,45]. In adrenalectomized rats, despite significantly reduced basal plasma IGF--1 levels, central NPY infusion was still able to inhibit the somatotropic axis, indicated by further reductions in plasma IGF--1.…”
Section: Discussionsupporting
confidence: 79%
“…These effects were restored by specific glucocorticoid replacement [31,34,45]. Other studies showed that adrenalectomy or administration of type II adrenal steroid receptor antagonists significantly attenuated or abolished the hyperphagia induced by acute central NPY injection in rats [16,23,34,37], although this was not consistent in all studies [43].…”
Section: Introductionmentioning
confidence: 93%
“…The fiber systems from the ARC and brainstem project into various hypothalamic sites previously implicated in regulation of feeding behavior (5)(6)(7)(8). In fact, not only administration into the cerebroventricular system (3, 9, 10) but microinjection of NPY into various hypothalamic sites (11)(12)(13) rapidly elicited robust feeding responses in rats. Continuous NPY infusion into the third cerebroventricle evoked continuous episodic feeding during the infusion and postinfusion intervals (14).…”
mentioning
confidence: 99%